The Complexity of Handling Posterior Subcapsular Cataract Case - Imelda, Eva; Siti Rain Jannah; Sarra Mutiara Adev; Toshniwal, Navneet Shamsundar (Heca Sentra Analitika, 2023)
Cataracts or “katarrhakies” in Greek means waterfall. This term is used because the vision in cataract patients is described as a closed waterfall due to the clouding of the lens. PSCs (posterior subcapsular cataracts) might cause symptoms within months. and can cause worse visual disturbances compared to other types of senile cataracts. A 63-year-old man came to the Department of Ophthalmology at RSUD Dr. Zainoel Abidin with a chief complaint of blurry vision in both eyes since two years ago and felt more severe in the left eye. The patient also complained of difficulty seeing an object and reading at close range. On physical examination, a cloudy lens was found in the central posterior part of his both eyes the iris shadow test of both eyes was positive. The patient was diagnosed with posterior subcapsular cataract oculus dexter and sinister (ODS). The patient was planned to undergo phacoemulsification and intraocular lens (IOL) implantation in his left eye. The patient came back in the next couple weeks after surgery and it shows that his left eye visual acuity was 20/20 and the ocular anatomy was in good condition. Nowadays, phacoemulsification is still the first choice in PSC therapy. This type of cataract is difficult to treat because the cataract is still thin and the lens is mostly transparent, but it often causes glare and vision impairment which can interfere with daily activities.